Elderly patients with lower‐jaw mobility require careful food texture modification: A cohort study. (27th February 2019) - Wada, Mikio; Hanamoto, Akiko; Kawashima, Atsushi
Abstract: Background: Few studies have investigated the relationship between lower‐jaw mobility and oral ingestible food texture choices in elderly patients. This study aimed to evaluate whether lower‐jaw mobility affects levels of food texture modification. Methods: This prospective cohort study targeted inpatients aged ≥65 years with pneumonia or urinary tract infection from August 2014 through July 2015. We defined "lower‐jaw mobility" as movement of the lower jaw (more than about 1 cm) when gently supported from both sides of the mandibular angle with index fingers. The primary outcome was food texture at discharge, which was evaluated using "Japanese Dysphagia Diet 2013": non per os, codes 0‐4 (in the order of increasing swallowing difficulty), and normal meal. Results: We evaluated 38 patients in the mobility group (mean age: 86.5 years) and 251 patients in the nonmobility group (mean age: 83.2 years). Percentages of patients capable of ingesting each food texture were as follows (mobility vs nonmobility): normal meal, 5.3% vs 50.1%; code 4, 39.5% vs 31.9%; code 3, 5.3% vs 8.8%; code 2, 10.5% vs 4.4%; code 1, 2.6% vs 0.8%; code 0, 0.0% vs 0.4%; and non per os, 36.8% vs 2.8%. Food texture codes were lower in the mobility group ( P  < 0.001). These relationships remained significant even after adjusting for potential confounding factors in multivariate analysis ( P  < 0.001). Conclusion: Elderly patients with lower‐jaw mobility were restricted to texture‐modified foods. Lower‐jaw mobility can be assessed easily even by nonmedical personnel, and regular assessment could help identify elderly patients requiring dietary adjustment. Abstract : Elderly patients with lower‐jaw mobility were restricted to texture‐modified foods, with only a few patients taking normal meals.